Comprehensive characterization of γ-aminobutyric acid (GABA) production by Levilactobacillus brevis CRL 2013: insights from physiology, genomics, and proteomics - Cataldo, Pablo G.; Urquiza Martínez, María Paulina; Villena, Julio; Kitazawa, Haruki; Saavedra, Lucila; Hebert, Elvira M. (Frontiers in Microbiology, 2024)
Levilactobacillus brevis CRL 2013, a plant-derived lactic acid bacterium (LAB) with immunomodulatory properties, has emerged as an efficient producer of γ-aminobutyric acid (GABA). Notably, not all LAB possess the ability to produce GABA, highlighting the importance of specific genetic and environmental conditions for GABA synthesis. To elucidate the GABA-producing capabilities of L. brevis CRL 2013 and support its potential for safe application, a comprehensive genome analysis was undertaken. This study revealed the absence of antibiotic resistance genes and virulence markers, supporting its safety for potential probiotic applications. Furthermore, genome analysis identified genes encoding the glutamate decarboxylase system, essential for GABA biosynthesis from glutamate. This system comprises the glutamate decarboxylase enzyme and the glutamate:GABA antiporter. L. brevis CRL 2013 harbors two gad genes encoding glutamate decarboxylase enzymes, gadA and gadB. Notably, gadB is located adjacent to gadC, which encodes the glutamate:GABA antiporter. The gadA gene, however, resides separately and distantly on the chromosome (~634 kb). The transcriptional regulator gadR was also identified upstream of gadC. Transcriptional analyses demonstrated cotranscription of gadR with gadC.To further investigate the physiology of GABA production by L. brevis, a chemically defined culture medium (CDM) was optimized and supplemented with monosodium glutamate (MSG) to analyze its impact on GABA production. While glutamate supplementation alone failed to activate GABA synthesis in CDM, the addition of nutritional factors beyond the defined medium components, such as yeast extract (YE), significantly enhanced GABA production. Proteomic analysis revealed minimal differences between CDM cultures supplemented with MSG and those without MSG. However, YE supplementation triggered significant proteomic changes, including the upregulation of GadB, a key enzyme involved in GABA production. Additionally, transcriptional analysis confirmed the substantial increase in gadB and gadR expression upon YE supplementation, further supporting its role in activating the GABA production pathway.These findings provide valuable insights into the influence of nutrient composition on GABA production. They also unveil the potential of L. brevis CRL 2013 as a safe, nonpathogenic strain with valuable biotechnological traits which can be further exploited for its probiotic potential in the food industry.